A Comparison of conservative management versus appendectomy in uncomplicated acute appendicitis in pediatric age - Afzal, Jawad; Ur Rehman, Waqas; Saleem, Salman; Rehan, Muhammad; Talat, Nabila (ADVANCES IN BASIC MEDICAL SCIENCES, 2025)
OBJECTIVE: The objective of this study was to compare the outcome of conservative management (CM) of acute appendicitis (AA) versus appendectomy in uncomplicated appendicitis in the pediatric age group regarding resolution of symptoms and hospital stay. METHODS: This randomized controlled trial was conducted after IRB approval. A total of 122 patients were registered in this study and were randomly assigned into two groups by a ballot method (61 patients in each group): In group A, children were managed conservatively with antibiotics, and in group B, Patients underwent appendectomy. After treatment in both groups, the outcome was measured in terms of resolution of symptoms and hospital stay. RESULTS: Overall, there was a male predominance in the study population, with 58.2% males and 41.8% females. Both groups were comparable concerning the age of presentation (Group A: 111.4 ± 24.38 months vs Group B: 112.4 ± 30.3 months, p-value=0.883). In terms of hospital stay, Group A had a mean stay of 2.655 ± 0.834 days and Group B had a mean stay of 1.967 ± 0.682 days, with a p-value of 0.001. Among the patients in the conservative group, 85.2 %( n=52/61) showed resolution of symptoms, while 14.8% (9/61) had treatment failure. The rate of histologically confirmed negative appendectomy was 11.5% (7/61) in the appendectomy group, which was confirmed histologically. The histology of the nine individuals in the conservative group who underwent appendectomy was positive. On follow-up, one patient (1.85%) in the conservative management group presented with recurrence. While in the appendectomy group, 4 cases of wound infection and one case of prolonged ileus were presented (overall complication rate 8.2%). CONCLUSION: for suspected acute appendicitis, antibiotics are safe and effective and may avoid unnecessary appendectomy, decreasing the operation rate and surgical hazards.